The importance of pseudocapsule preservation during hysteroscopic myomectomy. (December 2019) - Tinelli, Andrea; Favilli, Alessandro; Lasmar, Ricardo Basil; Mazzon, Ivano; Gerli, Sandro; Xue, Xiang; Malvasi, Antonio
Abstract: Minimally invasive techniques for myomectomy are based on the rationale of preserving the myometrial integrity, in order to spare muscular and fibro-neurovascular myometrial fibers and ensure complete and bloodless myoma removal. Post-operative myometrial vascularization is crucial in injured muscle regeneration. The post-surgical myometrial healing is needful for uterine reproductive function. Neurotransmitters and neurofibers were analyzed in the myoma pseudocapsule surrounding fibroid. They activate signaling molecule synthesis and release which, in turn, promote cell activation and induce muscle regeneration and growth. Pseudocapsule damage during myomectomy may lead to a reduction of neuropeptides and neurofibers at the hysterotomic site, to a poor physiological myometrial healing, with more fibrosis due to hypoxia, ischemia and necrosis. These pathophysiological events cause deficit in myometrial neurotransmission, muscular impulse and contractility, with ultimately impaired uterine muscle function during pregnancy, labor and delivery. Hence, during myomectomy, all manipulations should be performed as precisely and bloodlessly as possible, avoiding extensive, high wattage diathermocoagulation or excessive tissue manipulation or muscular trauma. Any iatrogenic pseudocapsule damage may alter neurotransmitter function during successive myometrial healing, impacting negatively on uterine repair and on eventual pregnancies. Hence the reasoned myomectomy on a biological basis, the "intracapsular myomectomy", satisfied these surgical and physiological requirements. It was described precisely and firstly by the hysteroscopy, with the image magnification of the preservation of the myoma pseudocapsule. The "intracapsular hysteroscopic myomectomy" demonstrated the safe and effective removal of submucous myomas with intramural development. It allowed to completely remove the myoma in one or two surgical steps, saving the pseudocapsule and the surrounding healthy myometrium. The respect of the myometrium and the reduced thermal injury, a part the excellent outcomes in terms of surgical complications prevention, post-surgical fibrosis and intrauterine synechiae reduction, highlighted the physiological development of a successive pregnancy, without any myometrial complications during pregnancy, labor and delivery.